The effect of genetic variation on promoter usage and enhancer activity - Marco Garieri (Nature Portfolio, 2017)
Expression quantitative trait loci (eQTL) are widely studied, yet the mechanisms by which they exert their effects are largely unknown. Here, performing CAGE-seq on 154 lymphoblastoid cell lines, the authors map regulatory variants associated with promoter usage (puQTLs) and enhancer activity (eaQTLs).